Study of the Effect of Different Concrete Treatment Methods on Concrete Compressive Strength - Irawan Irawan saputra; Mirza Ghulam Rifqi; M. Shofi’ul Amin (Indonesian Society of Applied Science, 2020)
The process of bonding cement with water in the manufacture of concrete will cause side effects of rising temperature in concrete commonly called the hydration process. Heat hydration is too high can result in cracks in the concrete, therefore the need to do concrete maintenance work that serves to maintain the stability and availability of water in the concrete during the hydration process. The study uses cylinder-shaped test objects with a diameter of 15 cm and a height of 30 cm. There are 36 test objects and three types of treatments to be used in the study, i.e. soaking treatment, treatment wrapped with a plastic sheet, and curing compound treatment. Strong press testing is done at the age of 7, 14, and 28 days. Results of the study showed strong press pressing age 7 days concrete type with soaking treatment, treatment wrapped with a plastic sheet, and a consecutive curing compound treatment 0.38 MPa, 1.68 MPa and 2.29 MPa. Strong Test press Age 14 days concrete type with soaking treatment, treatment wrapped with a plastic sheet, and curing compound treatment consecutive 21.97 MPa, 21.59 MPa, 20.29 MPa. Strong Test Press Age 28-day type of concrete with soaking treatment, treatment wrapped with a plastic sheet, and the curing of the successive compound maintenance 25.89 MPa, 23.78 MPa, and 22.48 MPa.